Protection of piglets immunized with a cloned pseudorabies virus - ABDELWAHID, S. A.; ELJALII, IMA (Journal of the Hellenic Veterinary Medical Society, 2017)
The potential of pseudorabies virus (PrV) clone (mAlp) as an immunizing agem against Aujeszky’s disease (AD) in swine was invesτigaτed in this study. The pathogenicity, immunogenicity and protective efficiency induced by the virus were the major focus of the study. An indirect enzyme-linked immunosorbent assay was used to measure antibody responses to the virus. The virus was proved non-pathogenic for piglets up to the dose 10 plaque forming unit (p.f.u.). The antibody titres to the virus were correlated with the immunization dose. The difference in the antibody levels for the doses 10 and 10 p.f.u. was nonsignificant (p<0.01), but between the dose 10 and 10 , was significant (p<0.05). Following challenge of immunized animals with the virulent PrV-CD strain, total protection of piglets was observed even at the immunizing dose 10 p.f.u. In conclusion, PrVmAlp was non-pathogenic, highly immunogenic and protective against virulent PrV challenge in piglets, hence suggested as an efficacious and safe vaccine candidate against the disease.